Modeling and Harmonic Impact Mitigation of Grid-Connected SCIG Driven by an Electromagnetic Frequency Regulator - Juliano C. L. da Silva; Thales Ramos; Manoel F. Medeiros Júnior (Energies, 2021)
The power quality analysis is an essential issue in the integration of distributed energy resources to the grid. Recent standards regulate the harmonics disturbances due to the increasing penetration of intermittent energy sources interconnected with the grid employing power converters. This paper aims to analyze the power quality of an interconnected wind turbine system based on a Squirrel Cage Induction Generator (SCIG) driven by an Electromagnetic Frequency Regulator (EFR). The steady state of the EFR harmonic model is developed in the stationary frame based on the conventional induction generator modeling, which allows the study of the harmonic disturbances in the electrical and mechanical variables due to the PWM inverter of the EFR’s armature voltage. There is no electrical connection between the EFR and SCIG, and the results show that the inherent system inertia contributes to the mitigation of the harmonic content at the grid side generated by the switching. In addition to the steady-state results, the Total Rated Distortion (TRD), which considers the harmonics and interharmonics components, was computed and presented a good performance compared to the IEEE 1547 standard and real data extracted of a single Doubly Fed Induction Generator (DFIG). Finally, the harmonic performance of the proposed system was evaluated considering the impact of the equivalent Thevenin impedance of the grid at the Point of Common Coupling (PCC).